Artificial intelligence and the Fourth Industrial Revolution - Chakraborty, Utpal; Banerjee, Amit (Scientific consultant); Saha, Jayanta Kumar; Sarkar, Niloy; Chakraborty, Chinmay, 1984- (Singapore : Jenny Stanford Publishing, 2022)
This book presents the overall technology spectrum in artificial intelligence (AI) and the Fourth Industrial Revolution, which is set to revolutionize the world. It discusses their various aspects and related case studies from industry, academics, administration, law, finance, and accounting as well as educational technology. The contributors, who are experts in their respective fields and from industry and academia, focus on a gesture-recognition prototype for specially abled people; jurisprudential approach to AI and legal reasoning; automated chatbot for autism spectrum disorder using AI assistance; Big Data analytics and Internet of Things (IoT); role of AI in advancement of drug discovery; development, opportunities, and challenges of the Fourth Industrial Revolution; legal, ethical, and policy implications of AI; Internet of Health Things for smart healthcare and digital wellbeing; machine learning and computer vision; computer vision-based system for automation and industrial applications; AI-IoT in home-based healthcare; and AI in super-precision human brain and spine surgery. Buttressed with comprehensive theoretical, methodological, well-established, and validated empirical examples, the book covers the interests of a broad audience from basic science to engineering and technology experts and learners. It will be greatly helpful for CEOs, entrepreneurs, academic leaders, researchers, and students of engineering, biomedicine, and master's programs in science as well as the vast workforce and students with technical or non-technical backgrounds. It also serves common public interest by presenting new methods to improve the quality of life in general, with a better integration into society.
OCLC-licensed vendor bibliographic record.
Keywords: Artificial intelligence -- Industrial applications; Artificial intelligence -- Social aspects; Technological innovations -- Social aspects; Technological innovations -- Economic aspects; COMPUTERS / Artificial Intelligence